Investigating the relationship between the relative age effect and leadership behaviors among male ice hockey players. (September 2017) - Chittle, Laura; Horton, Sean; Weir, Patricia; Dixon, Jess C
This study examined the role of relative age on leadership behaviors among male house league ice hockey players. Athletes completed an online survey that solicited their birthdate along with their responses to the leadership scale for sport. As expected, the results of our analyses revealed no relative age effects. Captains scored significantly higher on the training and instruction, democratic behavior and social support dimensions of the leadership scale for sport. While there were significant multivariate differences between birth quartile and the dimensions of leadership, a relative weight analysis revealed that quartile of birth did not differ significantly on any of these dimensions. Thus, male house league hockey players are not (dis)advantaged in terms of their leadership behaviors as a consequence of relative age.